If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 3)(x) = 629 Reorder the terms: (3 + 2x)(x) = 629 Reorder the terms for easier multiplication: x(3 + 2x) = 629 (3 * x + 2x * x) = 629 (3x + 2x2) = 629 Solving 3x + 2x2 = 629 Solving for variable 'x'. Reorder the terms: -629 + 3x + 2x2 = 629 + -629 Combine like terms: 629 + -629 = 0 -629 + 3x + 2x2 = 0 Factor a trinomial. (-37 + -2x)(17 + -1x) = 0Subproblem 1
Set the factor '(-37 + -2x)' equal to zero and attempt to solve: Simplifying -37 + -2x = 0 Solving -37 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '37' to each side of the equation. -37 + 37 + -2x = 0 + 37 Combine like terms: -37 + 37 = 0 0 + -2x = 0 + 37 -2x = 0 + 37 Combine like terms: 0 + 37 = 37 -2x = 37 Divide each side by '-2'. x = -18.5 Simplifying x = -18.5Subproblem 2
Set the factor '(17 + -1x)' equal to zero and attempt to solve: Simplifying 17 + -1x = 0 Solving 17 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -1x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -1x = 0 + -17 -1x = 0 + -17 Combine like terms: 0 + -17 = -17 -1x = -17 Divide each side by '-1'. x = 17 Simplifying x = 17Solution
x = {-18.5, 17}
| 15(-0.8+3y)-20y=-7 | | 5x=15y-4 | | -2(10-5g)-4g=9+16g | | 15y=4+5(-1/5) | | 284-5x=40x+19 | | Y/3+7=12 | | 2(y-3)=-2 | | 4(y-2)=3(1.5+x) | | 6(t-5)+4t=5(2t+3)-12 | | 12(-4x+9)=16-2x | | 119=n-66 | | 15x-20(4/15+5/15x)=-7 | | -(8y+2)-(-7y-8)=3 | | 5y^3*3y^5= | | z=3+j | | 6x+7(4-x)=23 | | 2(7v-3)=22 | | t+27=15 | | y=x^5-2x^3+x-3 | | 4(2u-3)=24 | | (x-2)(x^2-4x+3)=0 | | log(2x+6)144=2 | | 4x+8+3x-5=129 | | 6(4-x)+7y=23 | | x^3+2x+8=0 | | x-3(9+x)=-11 | | x-3(9+x)=-11 | | 2(2x+3)-4(2-3x)=6+x | | 14-2(3p+p)=6(4+p) | | 5(2x+8)=7x+20 | | 0.05x+0.04y=420 | | -7-2x=-19 |